1987
DOI: 10.1016/s0022-5347(17)44289-3
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Biopsy after Definitive Treatment by Interstitial 125 Iodine Implant or External Beam Radiation Therapy

Abstract: The response to definitive radiation therapy of localized carcinoma of the prostate by 125iodine implantation or external beam radiotherapy was monitored by examining specimens from biopsies performed after treatment. We analyzed 126 biopsy specimens obtained 18 months or more after treatment: 71 were obtained from 109 patients treated by 125iodine and 55 from 197 patients treated by external beam radiotherapy. Thereafter, the disease status of these patients was examined at minimum 3-year intervals. No signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(23 citation statements)
references
References 22 publications
1
21
1
Order By: Relevance
“…[5][6][7][8][9] This broad range of recurrence rates is postulated to reflect patient selection criteria, the meticulousness with which the follow-up monitoring and biopsy was performed and variations in radiotherapy techniques applied. Risk factors for failure of radiation therapy have been identified, and include relative radioresistance of the prostatic carcinoma, failure to administer a cytotoxic dose to the entire gland, and limitations in the ability to increase dosing due to the potential of injuring surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9] This broad range of recurrence rates is postulated to reflect patient selection criteria, the meticulousness with which the follow-up monitoring and biopsy was performed and variations in radiotherapy techniques applied. Risk factors for failure of radiation therapy have been identified, and include relative radioresistance of the prostatic carcinoma, failure to administer a cytotoxic dose to the entire gland, and limitations in the ability to increase dosing due to the potential of injuring surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…4 Unfortunately, 25-71% of men will fail radiotherapy, many with isolated local recurrence. [5][6][7][8][9] The treatment options for locally recurrent disease following radical radiotherapy are limited: salvage surgery which has a high risk of significant and frequent morbidity, and hormone therapy which is noncurative. [10][11][12][13] Recently, cryosurgery has been advanced as an option for localized recurrence after radiotherapy based upon its successful application as a primary treatment for localized prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…After two years these figures were 38 percent (n=21) and 67 percent (n=6), respectively. Schellhammer et al 47 reported positive biopsy rates of 30 percent (n=40) for patients with stage B tumors and 43 percent (n=20) for patients with stage C tumors. The authors commented that grade was unpredictable in determining outcome in terms of postoperative biopsy results.…”
Section: Iodine 125 Retropubic Methodsmentioning
confidence: 99%
“…130 The recovery probability of early localized PC by radical prostatectomy or radical radiotherapy is quite high; however, between 35 and 61% of patients undergoing such treatment modalities are later found to have non-organ-confined disease or positive prostatic biopsies. [131][132][133] As a result, a significant proportion of patients seem to be left with residual disease, and currently no adjuvant or salvage therapy has been confirmed to be of promising benefit for treating these patients. Whereas androgen deprivation has remained the first line of therapy for advanced PC, other therapies are still required due to progression to an androgenresistant state and eventually loss of control in patients receiving hormonal therapy.…”
Section: Immunology and Immunotherapy Approaches E Elkordmentioning
confidence: 99%